Mapping the determinants of human immunodeficiency virus 2 for infectivity, replication efficiency, and cytopathicity. - Talbott, R (1993)
Human immunodeficiency virus 2 (HIV-2) ISY and the newly derived HIV-2KR are infectious molecular clones that yield viruses differing markedly in their abilities to infect and/or induce syncytia in various T- and monocytoid-cell lines. Chimeric viruses were constructed from these two viral genomes to localize the genetic determinants of some of these properties. Envelope sequences, particularly those spanning the CD4 binding site, appear to be critical for the ability of HIV-2KR to infect MOLT-4 clone 8 and SupT1 cells and to efficiently infect the H9 cell line. On the other hand, multiple determinants may contribute to cytopathicity (gp41 and nef) in H9 cells and replication efficiency in monocytic (THP-1) cells.